Cognitive Behavioural Models in Eating Disorders - Cooper, M (John Wiley and Sons, 2012)
A number of cognitive behavioural (CB) models and approaches have been suggested for eating disorders (EDs). This chapter provides an overview of those that have been published and applied, highlighting their specific and enduring contributions in the context of current practice and understanding of EDs. Following a brief summary of the empirical evidence that supports these models, including relevant treatment outcome studies, the case for a change in approach, while maintaining a cognitive behavioural focus, is presented, together with a brief summary of the supporting evidence. The chapter then outlines a revised cognitive model of bulimia nervosa (BN), together with some preliminary suggestions for a revised, cognitive model or understanding of anorexia nervosa (AN). Diagrammatic formulations are presented and a case material is used to illustrate the two models. Relevant empirical support for the proposed revisions is presented, and the implications for future research are summarized. © 2012 John Wiley and Sons, Ltd.